Multi-omics insight into muscle quality divergence between high-altitude Bayinbuluke sheep and low-altitude Turpan black sheep - Akhmiyati, Par Arshati; Chen, Bin; Yang, Yaling; Liu, Lingling; Liu, Wujun (Frontiers in Veterinary Science, 2025)
This study aimed to identify phenotypic biomarkers associated with high-altitude adaptation in Bayinbuluke sheep and to investigate the correlations between serum biochemical parameters and muscle transcriptomic, metabolomic, and proteomic profiles. Bayinbuluke sheep (raised at 3200 m) and Turpan black sheep (raised at−154 m) were selected for the experiment. The results demonstrated that, to adapt to the complex high-altitude hypoxic environment, Bayinbuluke sheep enhance glycolytic flux to rapidly generate energy, suppress intramuscular lipid synthesis, regulate lipid metabolic homeostasis to maintain energy balance, and remodel metabolic networks. Specifically, the GPAT3 gene promotes neutral cholesterol ester hydrolase 1 (NCEH1) through the glycerophospholipid metabolism pathway, facilitating the hydrolysis of cholesterol esters and fatty acid esters, thereby modulating systemic lipid metabolism. The FASN gene regulates energy metabolism via the AMPK signaling pathway, increasing the levels of glycolytic intermediates and markers such as nicotinamide adenine dinucleotide (NAD). Meanwhile, L-lactate dehydrogenase (LDHB) enhances the glycolytic process under hypoxic conditions through the HIF-1 signaling pathway, catalyzing the conversion between lactate and pyruvate in muscle tissue to produce energy, thereby supporting energy supply under high-altitude hypoxia. Additionally, the GSTA1 gene improves detoxification capability and antioxidant responses through the drug metabolism—other enzymes system, alleviating oxidative stress damage. This study systematically elucidates the molecular regulatory network underlying high-altitude adaptation in Bayinbuluke sheep, providing a theoretical foundation for enhancing the genetic adaptability of livestock resources in high-altitude environments.